2018
DOI: 10.1016/j.jhep.2017.08.023
|View full text |Cite
|
Sign up to set email alerts
|

IL-1 receptor like 1 protects against alcoholic liver injury by limiting NF-κB activation in hepatic macrophages

Abstract: In mild ALD, ST2 negatively regulates the inflammatory activation of hepatic macrophages, thereby protecting against alcohol-induced liver damage, whereas in the case of severe liver injury, the release of extracellular IL-33 may exacerbate tissue inflammation by triggering the canonical IL-33/ST2L signaling in hepatic macrophages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(35 citation statements)
references
References 42 publications
4
26
0
Order By: Relevance
“…Thus, we may speculate that by interfering with IL‐33, the increased sST2 levels further block bioactivity with respect to the function of IL‐33. Liver cirrhosis is the consequence of progressive fibrosis; the present study, in contrast to a recent report of IL‐33‐ST2 axis characteristics in a mouse model of AH and fibrosis, further extends the characteristics of the IL‐33‐ST2 axis in this type of patients.…”
Section: Discussionsupporting
confidence: 63%
See 3 more Smart Citations
“…Thus, we may speculate that by interfering with IL‐33, the increased sST2 levels further block bioactivity with respect to the function of IL‐33. Liver cirrhosis is the consequence of progressive fibrosis; the present study, in contrast to a recent report of IL‐33‐ST2 axis characteristics in a mouse model of AH and fibrosis, further extends the characteristics of the IL‐33‐ST2 axis in this type of patients.…”
Section: Discussionsupporting
confidence: 63%
“…The IL-33-ST2 axis has been reported to be involved in a variety of liver diseases; recently, an unanticipated role of this axis has been demonstrated in a mouse model of ALD. 25 In the present study, we further investigated the characteristics of the IL-33-ST2 axis in a cohort of patients with ALD. We found that serum sST2, but not IL-33, levels were increased in patients with ALD.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…[14][15][16][17] IL-33 participates in the regulation of gene expression but is also considered a damage-associated molecular pattern (DAMP) released after cell injury and/or necrosis especially in tissue macrophages. 18 Binding of IL-33 to the transmembrane form of ST2 (suppression of tumorigenicity 2) (ST2L) leads to subsequent activation of multiple intracellular signaling pathways which depend on cell type and location. In addition to IL-33/ST2 signaling on the cell surface, the ST2 gene also encodes a soluble form of the protein (sST2) lacking the transmembrane domain and acting as a decoy receptor for IL-33, inhibiting signal transduction of this pathway.…”
Section: Introductionmentioning
confidence: 99%